Obtención de parámetros de pan fortificado a partir de pulpa del plátano pildorita (Musa alinsanaya) - Angulo López, Patricia Marianela (2024)
The work had as main raw material a variety of plantain, Pildorita variety (Musa alinsanaya), which in its chemical physical analysis reported the following contents in 100 grams of edible sample or fresh sample: Moisture; 68.20%, ashes; 0.82%, fats; 0.01%, proteins; 1.51%, carbohydrates; 19.80%, energy expressed as Kcal; 85.29, soluble solids; 15.20, vitamin C; 8. 50 mg/100 grams of fresh raw material, and pH; 4.00, having the purpose of obtaining a type of bread (biscocho), which followed a standard flow chart with a formula of (5% banana pildorita dough + 95% wheat flour), for this type of bread: raw material, formulation dosage, mixing/kneading, refining/stretching, weighing I, division, molding, standardized/roasting, fermentation, baking, cooling, weighing II, fortified breads. For which the physical-chemical analyses of the three treatments (T1, T2 and T3): moisture; 30.22, 29.65, 27.32, ash; 1.63, 1.75, 1.81, fat; 4.92,4.60, 4.40, protein; 9.48, 9.39, 9. 08, carbohydrates; 53.75, 54.60, 57.9, energy; 297.20, 297.36, 305.48, titratable acidity (expressed as H2SO4) 0.08,0.09, 0.10, pH; 6.79, 6.77, 6.76, iron content; 6.40, 8.41, 8.40. The microbiological tests were then carried out, reporting for each treatment 10, 10, <1 for molds, 15, <10 and 4x102, for yeasts, similarly the sensory test was carried out evaluating color, odor, flavor, texture, and general appearance, where it was concluded that the treatment (T1), and the statistical tests corroborate this conclusion of the preference for this treatment.